Higher education in development : lessons from sub-Saharan Africa - Ashcroft, Kate; Rayner, Philip (Emerald Publishing Limited : Information Age Publishing, 2011)
This book will interest readers learning about or developing strategies for improving higher education systems and institutions in developing countries.It provides an insight into sub-Saharan African higher education systems and sets out the ways that they are developing and changing. It explores the dilemmas inherent in a context of scarce resources with increasing and urgent demands for a more professionalized workforce and expert services. It examines the factors inhibiting development such as HIV/AIDS, gender issues, historical conflicts, cultural attitudes inimical to innovation, the challenges created by poor infrastructure, and the history of colonialism and authoritarianism and their legacy of centralized control and lack of autonomy and democracy.The book explores lessons from research into sub-Saharan African higher education that may be applied to other contexts. The authors have lived and worked in sub-Saharan Africa and the book draws on the authors' personal experience of higher education in Zambia, Ethiopia, The Yemen and their links in Mozambique and South Africa as well as extensive senior management experience and at the highest level within sub-Saharan higher education systems. It uses actual examples and a reflective 'case study' approach to describe reforms, and from these, develops ideas as to how to improve the effectiveness of higher education as a means to fight poverty.The book explores lessons from research into sub-Saharan African higher education that may be applied to other contexts. The authors have lived and worked in sub-Saharan Africa and the book draws on their personal experience of higher education in Zambia, Ethiopia, The Yemen and their links in Mozambique and South Africa. The authors also use their extensive management experience at the highest level within sub-Saharan higher education systems. The book includes actual examples and a reflective 'case study' approach to describe reforms, and from these, develops ideas as to how to improve the effectiveness of higher education as a means to fight poverty.